PENGARUH KEGIATAN PENYULUHAN DALAM PELAYANAN KESEHATAN PEDULI REMAJA (PKPR) TERHADAP PENGETAHUAN DAN SIKAP REMAJA TENTANG SEKS PRANIKAH DI SMAN 1 LUBUK DALAM KABUPATEN SIAK SRI INDRAPURA TAHUN 2013 - Nuzulia Rahayu; Yusniwarti Yusad; Ria Masniari Lubis (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2013)
Teenager are a large population of the world population. Adolescent health is largely determined by their behavior. Premarital sex is one of the warning teen issues today. Lack of knowledge and misinformation to be one of the causes of premarital sex among adolescent. PKPR is one of the activities undertaken by government to address youth issues. This research aimed to see the effect of the counseling in PKPR  on knowledge and attitudes teens about premarital sex. This study adopted a quasi experiment method with the approach pretest-posttest one group with sampling techniques using simple random sampling. The data analyzed by t-test and wilcoxon. The result showed an increase in knowledge and attitudes about premarital sex teens toward better after counseling activities . The test result obtained on the effect of counseling activities for adolescent knowledge and attitudes about premarital sex with p value = 0,001 < α= 0,05. It is expected that the health center care of performing routine PKPR activities such as counseling at school for at least sixth month and the school is expected to adding the productive health education in the subject. Key word: Counseling, PKPR, Knowledge, Attitudes, Teenagers, Premarital Sex